Psychological wellbeing, family cohesion, and purposeful life in male prisoners: A cross-sectional study - Ghazanfari, Hooshang; Miri, Sakineh; Taebi, Mozhgan; Farokhzadian, Jamileh (Frontiers in Psychiatry, 2023)
Background Psychological wellbeing, family cohesion, and purposeful life are important determinants of the prisoners’ overall wellbeing and health; therefore, their evaluation is extremely important in prisoners as a vulnerable group. Objective This study evaluated psychological wellbeing, family cohesion, purposeful life, and their correlations in male prisoners. Methods This cross-sectional study used simple random sampling to select 259 male prisoners. Data were collected using questionnaires of Ryff psychological wellbeing, Fischer family cohesion, and Crumbaugh and Maholick purpose in life. Results Majority of (78%) the participants were 20–40 years old and married (59%). The mean scores of psychological wellbeing, family cohesion, and purposeful life of the male prisoners were moderate. Psychological wellbeing was directly correlated to family cohesion in male prisoners, but it had no significant correlation with a purposeful life. Family cohesion was not significantly correlated to a purposeful life. Conclusion Regarding the moderate level of psychological wellbeing in prisoners, it is suggested to pay more attention to educational and supportive programs in prisons for promoting such indicators in prisoners.